2008
DOI: 10.1029/2007gl031926
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal P/Ca tracks upwelling in Gulf of Panamá coral: Evidence for a new seawater phosphate proxy

Abstract: [1] The supply of limiting nutrients to the low latitude ocean is controlled by physical processes linked to climate variations, but methods for reconstructing past nutrient concentrations in the surface ocean are few and indirect. Here, we present laser ablation mass spectrometry results that reveal annual cycles of P/Ca in a 4-year record from the scleractinian coral Pavona gigantea (mean P/Ca = 118 mmol mol À1 ). The P/Ca cycles track variations in past seawater phosphate concentration synchronously with sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 30 publications
4
49
0
1
Order By: Relevance
“…The skeletal element ratio P/Ca was shown to track annual upwelling cycles in a single Pavona gigantea coral over a 4-year record (LaVigne et al, 2008). This study also revealed that $90% of coral skeleton P is incorporated as an intracrystalline phase resistant to solution cleaning of finely ground coral aragonite.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The skeletal element ratio P/Ca was shown to track annual upwelling cycles in a single Pavona gigantea coral over a 4-year record (LaVigne et al, 2008). This study also revealed that $90% of coral skeleton P is incorporated as an intracrystalline phase resistant to solution cleaning of finely ground coral aragonite.…”
Section: Introductionmentioning
confidence: 74%
“…Multi-year P/ Ca records were averaged to acquire mean skeletal P/Ca for two Montastrea faveolata (Biscayne National Park, FL; and Martinique, Caribbean) and five Porites lutea (Gulf of Aqaba/Eilat, Red Sea; Rarotonga and New Caledonia, South Pacific; Christmas Island and Fanning Island, Central Equatorial Pacific) colonies (Table 1; Linsley et al, 2000;Desenfant, 2004 ;Nurhati et al, 2009). Since skeletal P sampled below the organic tissue layer has been shown to be resistant to rigorous chemical cleaning (LaVigne et al, 2008), the powders extracted from distilled-water rinsed slabs were not cleaned chemically prior to analysis for the globally distributed samples. Mean P/Ca values for Montastrea sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[165][166][167][168][169][170][171] The latter sample materials can reflect the environmental status in water in their element/Ca ratios. 172 Sea water temperatures can be calculated from Mg/Ca ratios in foraminifera since the uptake of Mg into foraminiferal CaCO 3 is temperature-dependent.…”
Section: Geological and Radionuclide Applicationsmentioning
confidence: 99%
“…The resulting nitrocellulose membranes were concomitantly incubated with a mixture of DOTA-lanthanide-labelled antibodies, i.e. 165 Ho-anti-BSA, 159 Tb-anti-casein and 169 Tm-antilysozyme and finally subjected to LA-ICP-SFMS. The lanthanide-specific signals were colour-coded and plotted (see Fig.…”
Section: Speciation Analysismentioning
confidence: 99%